Effect of enzymatic pretreatment on solubilization and volatile fatty acid production in fermentation of food waste - Kim, H J (Water science and technology : a journal of the International Association on Water Pollution Research, 2005)
Food waste can be a valuable carbon source in biological nutrient removal (BNR) systems because of the high C/N and C/P ratio. However, pretreatment is necessary to promote hydrolysis of food waste because of the high concentration of volatile solids associated with organic matter. The influence of the enzymatic pretreatment on acid fermentation of food waste was investigated in this study. Solubilization of particulate matter in food waste was carried out using commercial enzymes. The acidification efficiency and the volatile fatty acid (VFA) production potential of enzymatically pretreated food waste were examined. The highest volatile suspended solid (VSS) reduction was obtained with an enzyme mixture ratio of 1:2:1 for carbohydrase: protease: lipase. An optimum enzyme dosage for solubilization of food waste was 0.1% (V/V) with the enzyme mixture ratio of 1:2:1. In the acid fermentation of enzymatically pretreated food waste, the maximum VFA production and the highest VFA fraction in soluble COD (SCOD) were also achieved at 0.1% (V/N) of total enzyme dosage. Increase in VFA production at this level of enzyme dosage was over 300% compared with the control fermenter. The major form of VFA produced by fermentation was n-butyrate followed by acetate